Research on Design Method of Cathode Profile for High Precision Electrolytic Machining of Spur Face Gear - Wei Jiang; Yan Cao; Feng Jia; Liang Huang (Jixie chuandong)
The tooth surface of the spur face gear is a kind of complex space curved surface, in order to realize the batch machining of complex space curved surface products with difficult cutting materials, the main technology of electrolytic machining is mainly used at present. Considering that electrolytic machining has some problems such as low efficiency of cathode design and difficult to guarantee the design accuracy in the machining of complex dissimilar surface products, an intelligent design method of cathode profile based on the characteristics of standard cathode is presented. Firstly, based on complex tooth surface grid planning principle, the coordinate of each sampling tooth surface is calculated by section lofting method. Secondly, by analyzing the curvature radius of each tooth surface sampling point, the design scheme of the corresponding cathode tool profile is constructed based on the theory of electrolytic machining equilibrium gap theory. Finally, using the GUI human-computer interface in Matlab, the intelligent cathode profile design system for spur face gear is constructed. Meanwhile the experimental shows that the machining accuracy of the cathode surface designed by the system is up to IT8.